Factors contributing to increased Cases of Malaria in Children below Five years in Moyo General Hospital, Moyo District. A Cross-sectional Study. - Tamale , Robert; Mubangizi , Prosper (Student’s Journal of Health Research Africa, 2022)
Background: The purpose of the study was to determine the factors contributing to increased cases of malaria in children below five years in Moyo general hospital, Moyo District. Methodology: The study employed a cross-sectional study with a simple random technique as a sampling technique. Data was collected from a sample of 50 respondents using a questionnaire written in the English language as a data collection tool; later analyzed manually by use of tally sheets presented in tables and figures for easy interpretation of findings. Results: Findings in regards to health facility-related factors showed that; (52%) had never acknowledged enough counseling services about malaria, (62%) reported that they don’t get enough access to anti-malaria drugs at the health facility, (76%) reported > 5km as the distance from their homes to the nearby health facility, (68%) reported that they don’t pay for access to health care services, (60%) visit a doctor when their children’s health does not improve, and (54%) reported that the attitude of health workers towards the provision of health care services it is good. Conclusion: Poor health-seeking behaviors, low levels of employment, inadequate access to mosquito bed nets, irregular use of mosquito nets among those who had access to them, low uptake of interior spraying, location of respondents’ homes, poor housing infrastructures, poor waste management behaviors, long distances and inadequate access to ant- malaria drugs were the major factors that contributed to increased cases of malaria among children below five years. Recommendation: Health workers at Moyo general hospital should intensively enhance access to information on signs and symptoms of malaria, consistent use of ITNs, and environmental management. So that suspicious cases can be quickly identified, improve on health-seeking behaviors of the people and hence minimize the burden of malaria.